2021
DOI: 10.1089/met.2020.0032
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Serum Gamma-Glutamyl Transferase Level and Impaired Fasting Glucose Among Chinese Community-Dwelling Adults: A Follow-Up Observation of 6 Years

Abstract: Objective: We aimed to investigate the relationship between serum gamma-glutamyl transferase (GGT) and fasting blood glucose (FBG) levels, as well as the cumulative risk of impaired fasting glucose (IFG) regulation in the Chinese adult population after 6 years of follow-up. Methods: A total of 1360 apparently healthy Chinese men and women who completed a community-based health examination survey and did not have IFG in central China in 2010 and 2016 were included in this study. The patients were divided into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
3
2
0
Order By: Relevance
“…Relevant studies have shown that patients with IFG possess a significantly higher risk of developing diabetes 15 . In a previous study, we confirmed that serum GGT levels were positively correlated with IFG in Chinese adults, and this trend was not affected by other confounding factors 16 . The present 6‐year follow‐up study in China evaluated the relationship between GGT and FBG.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Relevant studies have shown that patients with IFG possess a significantly higher risk of developing diabetes 15 . In a previous study, we confirmed that serum GGT levels were positively correlated with IFG in Chinese adults, and this trend was not affected by other confounding factors 16 . The present 6‐year follow‐up study in China evaluated the relationship between GGT and FBG.…”
Section: Discussionsupporting
confidence: 81%
“…Studies have shown that individuals with IFG are at a higher risk of subsequent diabetes [14] . Our previous study confirmed that serum GGT levels are positively associated with IFG in Chinese adults, independent of other confounding factors [15] . Our recent 6-year follow-up study conducted in Chinese to further evaluate the relationship between GGT and fasting glucose.…”
Section: Discussionsupporting
confidence: 79%
“…High levels of GGT have been found to be associated with increased risk of MetS and impaired fasting glucose [78,81,82]. Our participants' GGT levels in ketosis (P1 and P3) and SuK (P2) were within standard reference ranges.…”
Section: Liver Markers 351 Ggtsupporting
confidence: 47%
“…In addition, a result of the Korean Genome and Epidemiology Study including 7,739 nondiabetic adults aged 40 to 69 years living in the community confirmed that higher serum γ-GTP level was positively associated with incident diabetes [ 23 ]. In an observational study of 6 years in China, the cumulative incidence of IFG increased in the groups with higher γ-GTP level is a dose-dependent manner [ 24 ]. In Japan, several studies have shown that γ-GTP is positively correlated with the incidence of diabetes in both men and women [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%